2018
DOI: 10.1371/journal.pone.0196770
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of accuracy and recognition of three-dimensional computerized forensic craniofacial reconstruction

Abstract: Facial reconstruction is a technique that aims to reproduce the individual facial characteristics based on interpretation of the skull, with the objective of recognition leading to identification. The aim of this paper was to evaluate the accuracy and recognition level of three-dimensional (3D) computerized forensic craniofacial reconstruction (CCFR) performed in a blind test on open-source software using computed tomography (CT) data from live subjects. Four CCFRs were produced by one of the researchers, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
4
25
0
3
Order By: Relevance
“…In our study we found high concordance between both–as evidenced by both subjective visual evaluation and biometric analysis–though the match is not 100%. Interestingly, the range of concordance is in the same range as that given for forensic facial reconstructed cases where Miranda et al [ 19 ] confirmed a 63–73% concordance rate. Furthermore, this means that the portrait does, indeed, depict the infant.…”
Section: Discussionsupporting
confidence: 61%
“…In our study we found high concordance between both–as evidenced by both subjective visual evaluation and biometric analysis–though the match is not 100%. Interestingly, the range of concordance is in the same range as that given for forensic facial reconstructed cases where Miranda et al [ 19 ] confirmed a 63–73% concordance rate. Furthermore, this means that the portrait does, indeed, depict the infant.…”
Section: Discussionsupporting
confidence: 61%
“…The human face can be reconstructed manually or in a virtual environment based on the principles advocated by one of the three schools. The manual technique uses modeling material, such as plasticine, biscuit, or clay, while the computer-aided technique provides for the reconstruction in a virtual environment based on the scanning of the skull, using specific editing and modeling software [1,3,13,14]. Even free software can be used, which are able to produce 3D facial reconstructions with plausible levels of accuracy and likeness and may be recommended for forensic investigations [14].…”
Section: Introductionmentioning
confidence: 99%
“…The manual technique uses modeling material, such as plasticine, biscuit, or clay, while the computer‐aided technique provides for the reconstruction in a virtual environment based on the scanning of the skull, using specific editing and modeling software [1, 3, 13, 14]. Even free software can be used, which are able to produce 3D facial reconstructions with plausible levels of accuracy and likeness and may be recommended for forensic investigations [14]. Regardless of the chosen method, it will be significantly useful for the recognition of the recreated face by relatives or people close to the individual whose identity is being questioned in the civil and/or criminal sphere, provided that the best practices in the execution of the technique are respected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of facial approximation of the nose have shown discordant results in their levels of accuracy . Whereas Wilkinson concluded that the nose can be reconstructed with a high level of accuracy, other studies revealed that some parts of the reconstructed nose deviated more than 5.0 mm from the actual parts. Lee et al reconstructed the faces of three Korean subjects.…”
mentioning
confidence: 96%